Comparison between Pregnant Womenâ Preferences and Midwivesâ Performance in Prenatal Congenital Anomaly Screenings Counseling in Indonesia - Januraheni, Ni Luh Putu; Gau, Meei Ling (The Southeast Asian Journal of Midwifery, 2017)
Abnormalities are the fourth cause of infant and neonatal mortality in Indonesia. In this situation, midwives need to give clear information about anomaly prenatal tests. This studi aims to compare of pregnant womenâ preferences and midwivesâ performance about prenatal congenital anomaly screening counseling in Indonesia. The study was carried out at two health centres and two hospitals in Bali from July to September 2016, with 40 midwives and 200 pregnant women. The QUOTE prenatal questionnaire and a cross-sectional descriptive correlative design was used in this study. The result shows that education was the only one of pregnant women demographic data that significant to counseling anomaly screening. The performance of midwives was concluded to perform well on counseling, however as pregnant women perspective, the midwives performance was not as higher as midwives perspective on counseling. The midwivesâ performance and pregnant womenâ preferences were influenced by individual`s midwife factors on pregnant women-midwives relationship and decision making. Different result was found that health education was more influenced by different person of midwives. There was a different between pregnant womenâ preferences and midwivesâ performance about prenatal congenital anomaly screening counseling. The women-midwives relationship and decision making, the variance of midwifeâs individual different (within variance) was much higher than different midwives (between variance). In terms of health education subscale, the variance of different midwives performance of congenital anomaly screening counseling (between variance) was much higher than individual midwives (within variance).Keywords: Pregnant women, Midwives, Prenatal Counseling